Low-Molecular-Weight Heparin Anti-Xa Guided Reversal of Apixaban With Prothrombin Complex Concentrate in a Patient on Hemodialysis. (April 2023) - Brummett, Christina M.; Dingman, James S.; Philip, George J.; Moran, David A.; Gilbert, Brian W.
The growing use of oral factor Xa (FXa) inhibitors in patients with chronic kidney disease (CKD), particularly the recent increased use of apixaban in patients with end-stage renal disease (ESRD), has created a new dilemma in the already controversial topic of oral FXa inhibitor reversal. With the limited availability of anti-Xa levels specific to oral FXa inhibitors and even scarcer availability of reversal data for patients on these agents with ESRD, ensuring adequate reversal is currently often solely guided by repeat imaging and changes in clinical status. Low molecular weight heparin (LMWH) anti-Xa levels have been used as a more commonly accessible test to guide the need for and efficacy of reversal of oral FXa inhibitors in patients with normal renal function. However, evidence supporting this technique is again lacking in patients with renal dysfunction. This case report focuses on the use of LMWH anti-Xa levels to guide reversal of apixaban in a patient with ESRD on hemodialysis and correlation of those levels to the patient's clinical status.